Shear Strength characteristics of gypseous Soil with Lime - Talib Kamel Qassim Al-Sheakayree (University of Thi-Qar Journal of Science, 2019)
Gypseous soils are abundant in Iraq, constitute over 33% of total surface area in Iraq. Thestructures that founded on these soils could face large damages due to dissolving of gypsum whensaturated in water.This study investigates the shear strength characteristics of gypseous soil withlime. The soil used was fetched from Al-Dour region (66% gypsum content). This soil wastreated with different percentages of Lime (0.5, 1.5, 2.5 and 5%). Test results pointed out that thebest treatment percentage to be 1.5.shear strength tests (direct shear tests) conducted in order tostudy the shear strength characteristics of gypseous soil with Lime and to find the suitablepercentage of Lime to improve the shear strength characteristics of gypseous soil against theeffect of soaking water, in order to attain a sort of simulation with the field conditions; both theunit weight and the water content of the natural soil are kept equal to the field values. All treatedspecimens were cured at 370C for 7 days before performing these tests.The results of shear strength tests show that the addition of Lime to the gypseous soil increasestheir strength to an optimum value and then decreases.